The perils of recreational marijuana use: relationships with mental health among emergency department patients - Catherine A. Marco; John Paul Detherage III; Ashley LaFountain; Megan Hanna; Justin Anderson; Rachel Rhee; Jacqueline Ziegman; Dennis Mann (Journal of the American College of Emergency Physicians Open)
Abstract Introduction Marijuana is a commonly used drug in the United States. Many states have legalized the recreational use of marijuana. The effects of marijuana on mental health are unknown. Methods In this prospective survey study, eligible participants included ED patients age 18 and older, who had ever used recreational marijuana. A survey instrument was developed, piloted, and revised. Data collected included reasons for marijuana use, marijuana's perceived effectiveness, and history of mental health conditions, including depression, anxiety, and suicidal thoughts. Results Among 303 participants (86% response rate), the median age of first marijuana use was 16 ([IQR 14, 19], range 6–65). The most commonly cited reasons for marijuana use included recreational use (70%; n = 211), to treat anxiety (30%; n = 89), to treat pain (25%; n = 74), and to treat depression (17%; n = 51). Mental health issues were common in the study population. A majority of patients reported anxiety in the last 30 days (59%; n = 176), and a significant minority of patients reported serious depression in the last 30 days (46%; n = 137). Some patients reported suicidal thoughts in the last 30 days (9%; n = 29). Participants who used marijuana more frequently reported more days of anxiety (median 15.5, compared to 1; P = 0.001). Among participants with mental health conditions, most began using marijuana before the onset of the mental health conditions (77%, n = 167). Earlier age of starting to use marijuana was correlated with higher number of years of anxiety or tension in lifetime (r = −0.11, P = 0.05, n = 301). Perceived effects of marijuana use on mental health were variable. Most participants stated that marijuana improved their mental health (62%; n = 163), and some reported that marijuana did not improve their mental health (37%; n = 98). Conclusions Many ED patients have used marijuana, either currently or in the past. Mental health conditions are also common, including anxiety, depression, and suicidal thoughts. Most participants reported marijuana use starting at an age under 18. Marijuana use preceded the onset of mental health conditions in the majority of participants.